Perception on Adoption and Application of Web 2.0 Technologies in Selected Academic Libraries in Tanzania - Mwantimwa, Kelefa; Nkhoma-Wamunza, Alice (University of Dar es Salaam Library Journal, 2017)
The main objective of the present study was to find out perceptions of librarians regarding integration of Web 2.0 technologies in library operations and services. Specifically, to determine the level of awareness, reasons for integration, and the challenges of Web 2.0 in supporting library operations and services at SUA and UDSM libraries. This study used mixed methods research design (both qualitative and quantitative). Non-probability sampling procedure was used to select the sample size of 40 librarians from the two university libraries (UDSM = 21, SUA = 19). Primary data was collected through face-to-face interviews and questionnaires with both open and closed-ended questions. SPSS was used to analyse the descriptive statistics and the findings are presented in frequency tables and percentages. Pearson Chi-square test was used to establish the relationships between different variables. The key findings suggest that there was a significant positive correlation [R= .555, N= 40, p = .000] between awareness and use of Web 2.0 technologies in non-library operations and an insignificant negative correlation [R = -.142, N = 40, p = .383] for library operations and services. Also, the findings show that the majority (70%) of the librarians in the selected university libraries were of the opinion that effective integration of Web 2.0 technologies can strengthen library operations and services. Further, it was revealed that Web 2.0 technologies also pose major challenges in library operations and services. Finally, this study recommends that policy frameworks should be formulated to facilitate effective adoption and integration of Web 2.0 technologies in the library operations and services.